2010
DOI: 10.1590/s1807-59322010001200004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preoperative serum N-terminal pro-brain type natriuretic peptide on the postoperative outcome and survival rates of coronary artery bypass patients

Abstract: BACKGROUND:The N-terminal fragment of pro-brain type natriuretic peptide (NT-proBNP) is an established biomarker for cardiac failure.OBJECTIVE:To determine the influence of preoperative serum NT-proBNP on postoperative outcome and mid-term survival in patients undergoing coronary artery bypass grafting (CABG).METHODS:In 819 patients undergoing isolated CABG surgery preoperative serum NT-proBNP levels were measured. NT-proBNP was correlated with various postoperative outcome parameters and survival rate after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
(18 reference statements)
3
22
0
2
Order By: Relevance
“…They found that in selected patients with severe left ventricular dysfunction the procedure is valid and safe and promotes less mortality and morbidity, compared with conventional operations. Schachner et al [3] endeavored to determine the influence of preoperative serum N-terminal fragment of pro-brain type natriuretic peptide (an established biomarker for cardiac failure) on postoperative outcome and mid-term survival in 819 patients undergoing isolated coronary artery bypass grafting. They concluded that preoperative peptide levels > 502 ng/ml predict mid-term mortality after isolated coronary artery bypass grafting and are associated with significantly higher hospital mortality and perioperative complications.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%
“…They found that in selected patients with severe left ventricular dysfunction the procedure is valid and safe and promotes less mortality and morbidity, compared with conventional operations. Schachner et al [3] endeavored to determine the influence of preoperative serum N-terminal fragment of pro-brain type natriuretic peptide (an established biomarker for cardiac failure) on postoperative outcome and mid-term survival in 819 patients undergoing isolated coronary artery bypass grafting. They concluded that preoperative peptide levels > 502 ng/ml predict mid-term mortality after isolated coronary artery bypass grafting and are associated with significantly higher hospital mortality and perioperative complications.…”
Section: Kk and Rocha E Silva M -Cardiology In Brazilian Scientific Joumentioning
confidence: 99%
“…increased length of ICU stay and longer hospital stay. 5,7,14,15 The duration of mechanical ventilation is commonly interpreted as an important marker of disease severity. ROC curve revealed 12 hour postoperative BNP level of higher cut-point of 234 pg/ml had a sensitivity of 50%, a specificity of 89%, and the lower BNP cut-point of 142 pg/ ml had a sensitivity of 71.4%, and a specificity of 52.7%.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative levels of its sister compound, brain natriuretic peptide (BNP), have been used to predict postoperative mortality in patients undergoing cardiac surgery procedures, including CABG 41, 42. Additionally, studies on patients undergoing isolated CABG found associations between preoperative levels of NT‐ProBNP and postoperative mortality, prompting inclusion of preoperative levels of the biomarker into our models 16, 43, 44…”
Section: Discussionmentioning
confidence: 99%
“…Given NT‐proBNP's strong associations with heart failure, mortality attributable to cardiovascular events, and mortality after cardiac surgery, its inclusion in a prediction model of in‐hospital mortality may serve to improve the model's predictive ability 13, 14, 15, 16. Galectin‐3, a member of the lectin family of proteins, and ST2, a biomarker for cardiac stress, have also been found to be strongly associated with heart failure 17, 18, 19, 20, 21, 22.…”
Section: Introductionmentioning
confidence: 99%